Defining the maximum physiological parameters of men’s hearts in the transition from youth to old age - Szubert, Józef; Ziółkowski, Włodzimierz; Szymańska-Paszczuk, Alicja; Wieczorek, Wojciech; Szubert, Marietta (Old Age in the Stream of Life: Reflections on Old Age. Volume 2, 2019)
During the transition from youth to old age the maximum physiological parameters of men’s hearts are reduced. Based on the global experimental data refereeing to the cross-sectional studies and longitudinal changes in maximum physiological parameters of the heart in the aging process, using mathematical analysis and mathematical modeling and computer simulation, the authors have developed an innovative, comprehensive and reliable method for determining the maximum of physiological parameters of heart: cardiac output (COmax), heart rate (maximum heart rate), stroke volume (SVmax), difference arterio- venous oxygen saturation (AVDmax) and oxygen uptake (Vo2max).The developed methods allow presentation of every maximum physiological parameter of the heart for the large and average endurance of men: a graphical presentation (with the use of a graph), an analytical presentation (using a mathematical equation) and in the tabular form. Such development of the maximum of physiological parameters allows determination of all the maximum heart parameters of men at any age and of any physical condition in a cross- section of all the parameters of maximum heart: COmax, maximum heart rate, SVmax, AVDmax and Vo2max.